Analyzing the Universal Character of Tourist Sector in the Leningrad Region - Yu. Yu. Pavlova (Plekhanov Russian University of Economics, 2021)
The article studies the tourist sector as a factor of social and economic development of the region. The author gives a definition of the term ‘universal character of tourist sector', formulates key criteria meeting the principle of universality, on the basis of which the approach to region analysis was developed. This approach gives an opportunity to find the degree of customer satisfaction with tourist services and shows whether the region is ready for developing new tourist programs within the frames of traditional, special and rear types of tourism. As an example the article analyzes the universal character of tourist sector in the Leningrad region, which showed a number of problems. Proceeding from this the author proposes to design a mechanism of their solution at the expense of enlarging the list of tourist services offered to customer and improving their quality. By analyzing the universal character of tourist sector it will be possible to find out and eliminate drawbacks in the tourist sphere and in designing strategy of efficient development of tourism in the region aimed at building-up the tourist traffic, which could become a factor of its social and economic development.